2018
DOI: 10.1007/s00038-018-1182-7
|View full text |Cite
|
Sign up to set email alerts
|

The decline in adolescent substance use across Europe and North America in the early twenty-first century: A result of the digital revolution?

Abstract: Objectives Increases in electronic media communication (EMC) and decreases in face-to-face peer contact in the evening (FTF) have been thought to explain the recent decline in adolescent substance use (alcohol, tobacco, cannabis). This study addresses this hypothesis, by examining associations between (time trends in) EMC, FTF, and substance use in more than 25 mainly European countries. Methods Using 2002–2014 data from the international Health Behaviour in School-aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 34 publications
6
70
0
1
Order By: Relevance
“…A slight increase in spending time with parents was found in a Swedish study, yet this change was not independently related to the decline in adolescent drinking [17]. What did make a difference was a large reduction in leisure-time social interaction with peers, which corroborates the results of other recent studies [14,[17][18][19]. However, the frequency of 'going out with friends' increased among Finnish youth in the 2000s, and paradoxically, Raitasalo et al [12] found that this change-in a statistical sense-explained some of the reduction in drinking.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…A slight increase in spending time with parents was found in a Swedish study, yet this change was not independently related to the decline in adolescent drinking [17]. What did make a difference was a large reduction in leisure-time social interaction with peers, which corroborates the results of other recent studies [14,[17][18][19]. However, the frequency of 'going out with friends' increased among Finnish youth in the 2000s, and paradoxically, Raitasalo et al [12] found that this change-in a statistical sense-explained some of the reduction in drinking.…”
Section: Introductionsupporting
confidence: 82%
“…It has been suggested that the rise in time spent on using information and communication technologies is important in this regard, as adolescents have become too busy with their media pursuits at the expense of activities, such as substance use, that typically occur in face-to-face social interactions [7,10]. However, the extant body of research does not support this assumption [19,33], and a possible role of the use of digital media in this regard may be complex [1].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, EIU seems to be distinct from traditional antisocial and problematic behaviours-our results showed that overprotection and increased time at home and in the family environment (in other words, decreased time in peer groups) increase EIU. The distinction between EIU and problematic adolescent behaviour is further supported by De Looze and his colleagues [54], who found that the overall trend in the decrease of substance use in recent adolescents is not related to increased use of digital media; thus, EIU is not simply a replacement for other forms of problematic behaviour. Despite the fact that some studies found an association between EIU and various conduct problems [55,56], and that problematic adolescent behaviours and EIU share some underpinnings with ADHD [57], our study points to the need for specific parenting approaches when addressing EIU and when addressing traditional problematic behaviours.…”
Section: Discussionmentioning
confidence: 87%
“…It has been suggested 45 that the rise in social media and screen time may be a factor in the decline in cannabis use by younger people: less time spent in face to face interactions with friends may reduce exposure to cannabis and other substances. However, a recent report suggests otherwise 46 .…”
Section: Discussionmentioning
confidence: 97%